Modern political economy: A brief history and some applications - Keith Jakee (Duke University, Center for the History of Political Economy (CHOPE), 2021)
This article - designed to give readers unfamiliar with public choice a historical overview and flavor for the kinds of problems considered - is divided into three main sections, "historical origins," the "modern founders of MPE," and a brief description of some "current issues" studied by public choice scholars.
Keywords: 330; Neue politische Ökonomie; Wirtschaftswissenschaft; Wirtschaftstheorie; Ökonomische Ideengeschichte; Theorie